ESTUDO DO COMPORTAMENTO DE Macrobrachium brasiliense (Heller, 1862) (Crustacea: Palaemonidae) DIANTE DE “Corydalus sp.” (Megaloptera:Corydalidae) EM CATIVEIRO. - COSTA, Marina Machado; NAKAGAKI, Kelly Makoto (ANAIS DO ENIC, 2017)
-